Artificial intelligence: the future of urinary stone management?. Issue 2 (March 2020) - Jahrreiss, Victoria; Veser, Julian; Seitz, Christian; Özsoy, Mehmet
Abstract : Purpose of review: To investigate the application of artificial intelligence in the management of nephrolithiasis. Recent findings: Although rising, the number of publications on artificial intelligence for the management of urinary stone disease is still low. Most publications focus on diagnostic tools and prediction of outcomes after clinical interventions. Artificial intelligence can, however, play a major role in development of surgical skills and automated data extraction to support clinical research. Summary: The combination of artificial intelligence with new technological developments in the field of endourology will create new possibilities in the management of urinary stones. The implication of artificial intelligence can lead to better patient selection, higher success rates, and furthermore improve patient safety.